2021
DOI: 10.1016/j.isci.2021.102435
|View full text |Cite
|
Sign up to set email alerts
|

The USP7-TRIM27 axis mediates non-canonical PRC1.1 function and is a druggable target in leukemia

Abstract: Summary In an attempt to unravel functionality of the non-canonical PRC1.1 Polycomb complex in human leukemogenesis, we show that USP7 and TRIM27 are integral components of PRC1.1. USP7 interactome analyses show that PRC1.1 is the predominant Polycomb complex co-precipitating with USP7. USP7 inhibition results in PRC1.1 disassembly and loss of chromatin binding, coinciding with reduced H2AK119ub and H3K27ac levels and diminished gene transcription of active PRC1.1-controlled loci, whereas H2AK119ub … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 93 publications
3
21
0
Order By: Relevance
“…Interestingly, tight control of p53 levels in muscle progenitors is pivotal for the regulation of differentiation and return to quiescence ( Flamini et al, 2018 ), leaving open the question regarding USP7’s role during this process. USP7 can also regulate gene expression through its interactions with Polycomb Repressor Complex (PRC) components and other epigenetic regulators ( Inoue et al, 2015 ; Lecona et al, 2015 ; Yamaguchi et al, 2017 ; Maat et al, 2021 ). Thus, it is possible to speculate that USP7 promotes differentiation by 1) controlling p53 levels, 2) interacting with specific transcriptional regulators such as Myogenin, and 3) by stablishing a favorable epigenetic landscape for the muscle genetic program.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Interestingly, tight control of p53 levels in muscle progenitors is pivotal for the regulation of differentiation and return to quiescence ( Flamini et al, 2018 ), leaving open the question regarding USP7’s role during this process. USP7 can also regulate gene expression through its interactions with Polycomb Repressor Complex (PRC) components and other epigenetic regulators ( Inoue et al, 2015 ; Lecona et al, 2015 ; Yamaguchi et al, 2017 ; Maat et al, 2021 ). Thus, it is possible to speculate that USP7 promotes differentiation by 1) controlling p53 levels, 2) interacting with specific transcriptional regulators such as Myogenin, and 3) by stablishing a favorable epigenetic landscape for the muscle genetic program.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Meanwhile, a proteomic study reported USP7 as a stable interactor of the Polycomb repressive complex PRC1.1. Notably, USP7 inhibitors strongly inhibited AML cell lines and primary AML cells proliferation in vitro, also independently of TP53 status, and significantly delayed leukemia development in a human MLL-AF9 xenograft mouse model [296].…”
Section: Deubiquitinating Enzymes In Hscs Genome Stabilitymentioning
confidence: 93%
“…As mentioned above, the critical cellular roles of USP7 and the effects of first-generation USP7 inhibitors in MDS/AML cellular models [263][264][265] support further research. Promisingly, the novel and more specific USP7 inhibitor FT671 was highly effective in impairing the growth of primary AML cells [296].…”
Section: Are Dubs Possible Therapeutic Targets?mentioning
confidence: 99%
“…the histone deacetylases HDAC1 and HDAC2 and the H3K36me2 demethylase KDM2B), and proteins that regulate PRC1 activity (e.g. the ubiquitin C-terminal hydrolase ubiquitin-specific protease 7 [USP7] that prevents self-ubiquitination of RING1 and PCGF to stabilize the complex and thus regulates H2A monoubiquitination levels [ de Bie et al., 2010 ; Maertens et al., 2010 ; Hu et al., 2014 ; Maat et al., 2021 ]) ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%